Answer:
8 i think
Step-by-step explanation:
Make a ratio, then cross multiply.
4/30=x/48
30x=4x48
30x=192
x=6.4
To attempt this algebraic equation we will be multiplying 4 to (3 - x) bracket so as to form the term on L.H.S.
![:\implies\tt{4(3 - x) = (1 - 2x)}](https://tex.z-dn.net/?f=%3A%5Cimplies%5Ctt%7B4%283%20-%20x%29%20%3D%20%281%20-%202x%29%7D)
![:\implies\tt{(12 - 4x) = (1 - 2x)}](https://tex.z-dn.net/?f=%3A%5Cimplies%5Ctt%7B%2812%20-%204x%29%20%3D%20%281%20-%202x%29%7D)
![:\implies\tt{12 - 4x = 1 - 2x}](https://tex.z-dn.net/?f=%3A%5Cimplies%5Ctt%7B12%20-%204x%20%3D%201%20-%202x%7D)
Combining like terms, we get,
![:\implies\tt{12 - 1 = - 2x + 4x}](https://tex.z-dn.net/?f=%3A%5Cimplies%5Ctt%7B12%20-%201%20%3D%20%20-%202x%20%2B%204x%7D)
![:\implies\tt{11 = 2x}](https://tex.z-dn.net/?f=%3A%5Cimplies%5Ctt%7B11%20%3D%202x%7D)
![:\implies\tt{2x = 11}](https://tex.z-dn.net/?f=%3A%5Cimplies%5Ctt%7B2x%20%3D%2011%7D)
![:\implies\tt{x = \frac{11}{2} }](https://tex.z-dn.net/?f=%3A%5Cimplies%5Ctt%7Bx%20%3D%20%20%5Cfrac%7B11%7D%7B2%7D%20%7D)
![:\implies\tt{x = 5.5}](https://tex.z-dn.net/?f=%3A%5Cimplies%5Ctt%7Bx%20%3D%205.5%7D)
Answer:
your question is not complete or should I say not correct ☺️
8x + c = 5d
First move c by subtraction it.
8x = 5d - C
Then move the 8 by dividing it.
x = 5/8d - C